Masyarakat Dayak di Kesultanan Kutai pada Abad Ke-19 - Ahyat, Ita Syamtasiyah (UI Scholars Hub, 2010)
The Dayak people of Kalimantan, who have occupied in the territory of Kutai Sultanate, the water kingdom along the riverbank and the upper course of the Mahakam, live by trading in the river ways. The Dayak people consist of eleven tribes; the Kenyah, Kayan, Bahau, Tunjung, Benua, and Bentian, were only some of them. They were governed under the sovereignty of the Sultanate of Kutai which had made easier for the colonial government to subdue the territory. However, the people of Kutai found ways to accept the Dayak, and vice versa. They sold forest produce, such as resin, birds’ nests,rice, and wax. At the time when the Dutch annexed the area under her state, the Dayak was prohibited to do business, and the Dutch became the sole proprietor of the region, exploiting rattan besides others.